Transcriptomes Suggest That Pinniped and Cetacean Brains Have a High Capacity for Aerobic Metabolism While Reducing Energy-Intensive Processes Such as Synaptic Transmission - Geßner, Cornelia; Krüger, Alena; Folkow, Lars P.; Fehrle, Wilfrid; Mikkelsen, Bjarni; Burmester, Thorsten (Frontiers in Molecular Neuroscience, 2022)
The mammalian brain is characterized by high energy expenditure and small energy reserves, making it dependent on continuous vascular oxygen and nutritional supply. The brain is therefore extremely vulnerable to hypoxia. While neurons of most terrestrial mammals suffer from irreversible damage after only short periods of hypoxia, neurons of the deep-diving hooded seal (Cystophora cristata) show a remarkable hypoxia-tolerance. To identify the molecular mechanisms underlying the intrinsic hypoxia-tolerance, we excised neurons from the visual cortices of hooded seals and mice (Mus musculus) by laser capture microdissection. A comparison of the neuronal transcriptomes suggests that, compared to mice, hooded seal neurons are endowed with an enhanced aerobic metabolic capacity, a reduced synaptic transmission and an elevated antioxidant defense. Publicly available whole-tissue brain transcriptomes of the bowhead whale (Balaena mysticetus), long-finned pilot whale (Globicephala melas), minke whale (Balaenoptera acutorostrata) and killer whale (Orcinus orca), supplemented with 2 newly sequenced long-finned pilot whales, suggest that, compared to cattle (Bos taurus), the cetacean brain also displays elevated aerobic capacity and reduced synaptic transmission. We conclude that the brain energy balance of diving mammals is preserved during diving, due to reduced synaptic transmission that limits energy expenditure, while the elevated aerobic capacity allows efficient use of oxygen to restore energy balance during surfacing between dives.